Hydrogen-rich Syngas from Steam Gasification of Waste Biomass Materials through CO2 Capture and Use of Catalysts - Vamvuka, Despina; Panagiotidou, Stavroula; Orfanoudaki, Agapi (European Journal of Applied Sciences, 2024)
The exploitation of some abundant and low cost waste materials was investigated for production of clean energy carriers rich in hydrogen, in line with low-carbon and circular economy policies. Waste concrete fines were used together with CeO2 and Na2CO3 as catalysts in order to achieve an improved system performance at lower temperatures. The study focused on the effects of sorbent/biomass ratio, type and catalyst loading, as well as temperature on fuel conversion, product gas composition and heating value, syngas and hydrogen yield and energy recovery from the solid waste materials used. The experiments were conducted in a fixed bed system, following a two-step process for eliminating tar and increasing the reactivity of generated biosolid. Gas analysis was performed by a thermogravimetric-mass spectrometry unit. At a molar ratio Ca/C=1, the amount of CO2 captured between 700°C and 750°C was 83-95% and the concentration of hydrogen in the product gas increased by about 40%, achieving values 69.5% mol for winery waste fuel and 59.6% for helianthus waste at 750°C. CeO2 and Na2CO3 catalysts improved conversion, which was raised up to 91-100% on a daf basis. Na2CO3 catalyst presented a better overall performance at a loading of 20% wt. At 750°C the molar fraction of hydrogen in the gas mixture ranged between 73% and 96% for the two fuels, whereas the higher heating value of gas and syngas yield varied between 12.4-13.1 MJ/m3 and 1.86-4.94 m3/kg, respectively.